A COMPARATIVE ANALYSIS OF INCLUSIVE EDUCATION POLICIES IN DEVELOPING COUNTRIES: A SYSTEMATIC LITERATURE REVIEW OF IMPLEMENTATION AND CHALLENGES - Jackson Yumame; Mohammad Ahmad Bani Amer (CV. ADIBA AISHA AMIRA, 2026)
This article presents a comparative analysis of inclusive education policies in developing countries through a systematic literature review of their implementation and associated challenges. Inclusive education is viewed as a strategic effort to guarantee the right to education for all students without discrimination; however, its implementation in developing countries still faces various obstacles, such as limited human resources, insufficient teacher training, inaccessible infrastructure, limited funding, and social stigma toward students with special needs. The study’s findings indicate that the success of inclusive education implementation is significantly influenced by policy consistency, school readiness, government support, and the involvement of the community and parents. Furthermore, there is a significant gap between policy formulations at the national level and actual practices on the ground. Therefore, it is necessary to strengthen teacher capacity, provide adequate facilities and infrastructure, ensure sustainable funding, and establish more comprehensive evaluation mechanisms so that inclusive education can be implemented effectively and equitably.